Beach bags and burglaries - Howell, Dorothy (Dorothy A.) (Howell, Dorothy (Dorothy A.). Haley Randolph mystery, 2014)
Winning a vacation to a resort that caters to the whims of the rich and famous, Haley Randolph, while searching for the hottest beach bag, finds her dream holiday taking a murderous turn when she stumbles upon the body of a maid.